Peningkatan Kreativitas Masyarakat dalam Mengolah Limbah Sedotan Plastik Menjadi Tempat Tissue - Ema Wardana; Cintia Apsari; Afriana Afrianaa; Sapar Sapar; Samsinar Samsinar (LPPM Universitas Bumigora, 2023)
The use of plastic straws to make tissue box crafts that are worth selling. The purpose of the student creativity program - entrepreneurship (PKM-K) is to motivate students to become entrepreneurs in processing waste, especially into crafts that have market value, such as tissue box crafts. Plastic straw waste in the Palopo City environment is one of the elements that causes pollution which is not easy to decompose because it is made from plastic and is inorganic. Utilizing plastic straw waste into valuable products is a creative effort to reuse waste to preserve the environment and increase the economic value of waste that is no longer used. The methods used are the input, process (production), output and evaluation stages. The results of this program are input, conducting market surveys to determine market conditions. Next is a feasibility study of the business to be run. The last stage is the selection of materials and the provision of places as well as facilities and infrastructure to support the production process. Process (production), the process of making a tissue box starts from the preparation of materials and tools. Output, namely the craft of tissue holders that are ready to be used and marketed to consumers. The last is evaluation. At this stage, we will review any deficiencies that make consumers uncomfortable using our products. The conclusion of the PKM-K program is that the use of plastic straws to make tissue box crafts that are worth selling can provide skills to students, especially at the Muhammadiyah University of Palopo, to remain innovative and creative in processing plastic straw waste, providing opportunities for students to practice entrepreneurship with a comprehensive understanding of the concept of entrepreneurship, and build students' enthusiasm to stay in business.